Physicochemical and electrochemical properties of 1,1,2,2‐tetrafluoroethyl‐2,2,3,3‐tetrafluoropropyl ether as a co‐solvent for high‐voltage lithium‐ion electrolytes - Xia, Lan; Lee, Saixi; Jiang, Yabei; Li, Shiqi; Liu, Zhaoping; Yu, Linpo; Hu, Di; Wang, Shuhan; Liu, Yitong; Chen, George Z. (Wiley, 2019)
Although high voltage positive materials for high energy density lithium-ion batteries have gained a great attention, the lack of compatible electrolytes with sufficiently high oxidative stability to deliver an excellent cycling ability restricts theirpractical application. Fluorinated solvents are considered as promising candidates for high-voltage electrolyte solvents. In this study, we select 1, 1, 2, 2-Tetrafluoroethyl-2, 2, 3, 3-tetrafluoropropyl ether (TTE) with high boiling point, low cost and good SEI-filming ability as a co-solvent of fluoroethylene carbonate-based electrolytes and extensively investigate its physicochemical and electrochemical properties for its applications in high-voltage lithium-ion batteries. Our experimental results show that the TTE-containing electrolyte exhibits not only a high oxidative stability up to 5.5 V (vs. Li/Li+), but also excellent wettability with the separator. Except for the high discharge capacity and increased coulombic efficiency of the Li/LiNi0.5Mn1.5O4half-cells assembled with the TTE-containing electrolyte cycled between 3.0 and 4.9 V, the cell also displays a high rate capability. This work shows that partially fluorinated ethers, e.g. TTE, are promising cosolvent for high-voltage electrolytes that can enable commercial development of high energy density lithium-ion batteries.